The Chenopodiaceae-feeding gall midges (Diptera: Cecidomyiidae) of the Na’aman salt marsh, Israel - Dorchin, Netta; Freidberg, Amnon (Zootaxa, 2008)
The Na’aman marsh is the last existing coastal salt marsh in Israel, supporting a vulnerable community of rare plant and animal species. While the vertebrate and some invertebrate communities in the salt marsh have been relatively well documented, almost nothing is known about its insects. In an effort to illustrate the importance of conserving this unique habitat and as part of a study of the gall midges of Chenopodiaceae in Israel, we reared five cecidomyiid species from the halophytes Arthrocnemum macrostachyum, Atriplex portulacoides, Sarcocornia perennis, and Suaeda splendens that grow in the marsh, the latter two are rare plants in Israel. Three of the gall-midge species are described here as new to science and the other two, Baldratia salicorniae and Stefaniella brevipalpis, are redescribed and a lectotype and a neotype are designated for them, respectively. The gall midges develop in stems and/or leaves of their respective hosts and all appear to complete at least two generations a year. For all but one of the species, the Na’aman salt marsh is the only locality in Israel where they have been found.